Knowledge and attitude of pregnant women regarding mode of delivery in women referring to Dezful health centers - Amir Ali Akbari, S; Bahrami, N; Tork-Zahrani, Sh; Alavi- Majd, H (Advances in Nursing & Midwifery, 2009)
Background The significant increase in Cesarean delivery around the world turns this issue to a major health concern. In Iran, Cesarean rate is 3 to 4 times higher than what is recommended by WHO. Determining knowledge and attitude of people is the first step in developing and enacting educational programs for health promotion. Purpose This descriptive study was performed to determine knowledge and attitude of pregnant women referring to Dezful health centers regarding mode of delivery in 2008. Methods 120 women selected via quota sampling method participated in the study. A questionnaire completed by interviewing regarding demographic characteristics, knowledge about modes of delivery and attitude toward normal vaginal delivery (NVD) was used for data collection. Content and test-retest methods were used for its validity and reliability. Results Most subjects (54.2%) had moderate knowledge regarding mode of delivery. Their attitude (56.7%) toward NVD was neutral. Conclusion Since the majority of cases had moderate knowledge about modes of delivery and neutral attitude toward NVD, holding prenatal educational classes in this regard and supervision as well as follow-up for them are recommended. Keywords: Knowledge, Attitude, Modes of delivery.